3D DUTH wrestling dummy and training - Barbas, I.; Giannakou, E.; Aggeloussis, N.; Gourgoulis, V. (International scientific and professional conference on wrestling: "Applicable research in wrestling", 2017)
The purpose of the training partner 3D DUTH wrestling dummy is to allow wrestling athletes to train at full speed and full contact, to improve their technique along with their specific wrestling power and speed. Using this dummy many head snapping technical holds and head snap set-ups, used to attack the legs, can be perfected without the risk of injury. At the same time significant data of technical applications are recorded in a database and compared with a previous training session in order to improve the configuration of the training program. The 3D DUTH wrestling dummy is made of durable and flexible materials and has Wi-Fi and Bluetooth connectivity, a point-of-view camera, auditory stimulus, 6 visual stimuli sensors, 11 pressure sensors and 4 accelerometers which can wirelessly send data to a computer. With the measurement of the kinematic parameters and the help of an analysis system, the motion curves (graphs) that describe the motion of the individual parts of the body and especially the legs can be derived during the whole training session, using the 3D DUTH wrestling dummy, the athlete`s most valuable partner.